The rock star as contemporary cowboy: film mythology and ideology - Barry, Thomas J (Kansas State University, 2006)
This study examines the mythology of rock and roll stars in film. To accomplish this the narrative structures and ideological components of films about rock stars were identified and analyzed. There were two reasons for choosing this film genre. First, these films are specifically produced for a youth-oriented audience, an age demographic making the transition to adulthood. Because of this, these films provide commentary about social institutions and cultural values about finding a place in a market-based economy that is not as clearly transparent in other genres. Second, these films deal with society across historical time periods, starting with the inception of rock and roll in the 1950s through the present time. Because they cross multiple decades it is possible to analyze how the narrative structure and content of the films change across time and how these changes reflect changes in social conditions. The narrative structure of these films were identified and analyzed following the methodology laid out by Will Wright in Sixguns and Society (1975). The five narrative structures that were identified included, in chronological order, the reconciliation plot, the personal revival plot, the personal revival plot tragedy variation, the self-destruction plot, and the rejection plot. The journey the heroes in each plot take, along with the obstacles they face and how they find their place in society, coincide with historically situated cultural values and social conditions. Film content was analyzed through assessing how binary oppositions were resolved and the core themes represented. Both components, the narrative structures and binary oppositions, changed in ways reflective of the historical context in which the films were produced and reinforced particular ideological positions about cultural values, the youth, and the marketplace. While the hero's journey took different direction within each of the identified plots, they all contained a common thread – the rock star always finds a place in society by conforming to structural conditions instead of working to alter them.
Keywords: Mythology; Ideology; Rock star; Film; Sociology, General (0626); Sociology, Social Structure and Development (0700)